Respuesta :

Step-by-step explanation:

∫ t⁷ e^(-t⁴) dt

If x = -t⁴, then dx = -4t³ dt, and ¼ x dx = t⁷ dt.

∫ ¼ x eˣ dx

If u = ¼ x, then du = ¼ dx.

If dv = eˣ dx, then v = eˣ.

∫ u dv = uv − ∫ v du

= ¼ x eˣ − ∫ ¼ eˣ dx

= ¼ x eˣ − ¼ eˣ + C

= ¼ eˣ (x − 1) + C

Substitute back:

= ¼ e^(-t⁴) (-t⁴ − 1) + C

The procedure would be as demonstrated in the attachment(s). As you can see your solution will be,

[tex]\frac{1}{4}\left(-e^{-t^4}t^4-e^{-t^4}\right)+C[/tex]

Ver imagen Аноним
Ver imagen Аноним